2016
DOI: 10.1007/s00253-016-7321-2
|View full text |Cite
|
Sign up to set email alerts
|

Microwave and ultrasound pre-treatments influence microbial community structure and digester performance in anaerobic digestion of waste activated sludge

Abstract: Comparative analyses of bacterial and archaeal community structures and dynamics in three biogas digesters during start-up and subsequent operation using microwaved, ultrasonicated or untreated waste activated sludge were performed based on 454 pyrosequencing datasets of part of 16S ribosomal RNA sequences and quantitative PCR. The pre-treatment increased the solubility, and thus the availability of the substrate for microbial degradation and significantly affected the succession of the anaerobic community str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 70 publications
(75 reference statements)
1
7
0
Order By: Relevance
“…The relative abundance of Firmicutes increased from 14.8% ("M1-Control") to 21.6% and 28.4% in the digesters of "M2-80 • C" and "M3-160 • C", respectively. This increase is consistent with previous research conducted by Westerholm et al [18], which was related to a comparative analyses of bacterial and archaeal community dynamics in three mesophilic digesters during start-up and operation using non-irradiated and MW-irradiated WAS. Their results proposed that increased substrate availability induced by MW pretreatment stimulated growth of members within Firmicutes.…”
Section: The Relationship Between Process Stability and Microbial Community Structuresupporting
confidence: 93%
See 1 more Smart Citation
“…The relative abundance of Firmicutes increased from 14.8% ("M1-Control") to 21.6% and 28.4% in the digesters of "M2-80 • C" and "M3-160 • C", respectively. This increase is consistent with previous research conducted by Westerholm et al [18], which was related to a comparative analyses of bacterial and archaeal community dynamics in three mesophilic digesters during start-up and operation using non-irradiated and MW-irradiated WAS. Their results proposed that increased substrate availability induced by MW pretreatment stimulated growth of members within Firmicutes.…”
Section: The Relationship Between Process Stability and Microbial Community Structuresupporting
confidence: 93%
“…However, to our knowledge, a limited number of studies in the literature reported about the applications of Illumina sequencing technology in anaerobic sludge digestion [14,16,17]. Furthermore, there is very limited knowledge on bacterial and archaeal microbial community structures of anaerobic culture in AD utilizing MW-irradiated sludge [18,19], even though an extensive number of studies have examined the impact of MW pretreatment on sludge disintegration and many conventional operational parameters (e.g., solids destruction, biogas production, and digestate dewaterability) [3,10,13]. In this context, the objective of this study was to explore the impact of MW pretreatment on the relationship between process stability and microbial community structure in the mixed microbial culture samples from thermophilic and mesophilic anaerobic sludge digesters operated at high OLRs.…”
Section: Introductionmentioning
confidence: 99%
“…For microwaves, applying 2.62 kJ/g TS at a temperature of 80°C and 10 min of application time, and US pretreatment, applying 2.37 kJ/g TS at a temperature < 35°C, it was found that microwaves caused a fourfold to fivefold greater cell death, but this did not result in significantly different biodegradation (Cella et al, 2015). Westerholm et al (2016) made a similar observation. This suggests that both microwave and ultrasonic pre-treatment result in comparable outcomes regarding biodegradation.…”
Section: Limiting Factors Advantages and Perspectivesmentioning
confidence: 76%
“…Previous studies based on 16S rRNA gene amplicon sequencing showed that relative abundance of bacteria and archaea in digestion sludge microbiomes generally accounted for > 95% and < 5%, respectively [10,11], being further confirmed by recent metagenomics analyses [9,12]. In view of the bacterial community, Bacteroidetes, Proteobacteria, Spirochaetes and Firmicutes were generally the dominant phyla in sludge digesters, and most of them were fermentative bacteria with high compositional and functional redundancy [9,[13][14][15][16]. By contrast, the slow-growing acetogenic syntrophs and methanogenic archaea in digestion sludge were limited to several lineages [9,11].…”
Section: Introductionmentioning
confidence: 69%